Robot-assisted laparoscopic ureteroneocystostomy in adults: A single surgeon experience and literature review - Najib Isse Dirie; Shaogang Wang (Asian Journal of Urology)
Objective: To present our experience and technique with robot-assisted ureteroneocystostomy (RAUN) procedure in adults. Methods: Between February 2015 and August 2018, a total of 30 (34 ureters) patients who underwent RAUN surgery under a single surgeon were retrospectively reviewed. Perioperative data such as age, sex, body mass index (BMI), American society of anesthesiologists score, estimated blood loss, surgical technique, operative time, complications, length of hospital stay, and stent removal time were recorded. During the follow-up, patients underwent renal function test, urinalysis, and renal ultrasound examination for evaluation. Success was defined as symptomatic and radiologic relieve. Lastly, a literature search was conducted to review all published articles regarding RAUN surgery in adults. Results: The patients’ mean age, BMI, EBL, operative time, and follow-up period were 45.4 years, 23.1 kg/m2, 65.6 mL, 182.9 min, and 21.3 months, respectively. The two most common indications for the surgery were benign ureteral strictures and ureteric injuries secondary to a previous radical hysterectomy. Of the 34 cases, 26 (76.5%) and 8 (23.5%) patients received primary RAUN and RAUN with psoas hitch technique, respectively. Refluxing RAUN method was performed in all cases. No intraoperative complications were found. Two patients had a radiologic and symptomatic recurrence; one was managed with a repeat surgery while the other received ureteral dilatation treatment. Conclusion: Both our study and the published literature showed that RAUN is a safe, less invasive, and effective surgical technique that can easily replicate the open ureteroneocystostomy for managing lower ureteral diseases. Keywords: Outcomes, Psoas hitch, Robot-assisted, Ureteroneocystostomy